Trends in the internationalization of higher education: A review of internationalization at home in China and other countries - Nannan Wang; Siew, Nyet Moi; Nan Zhang (Human Resource Management Academic Research Society, 2025)
Internationalization at Home (IaH) has emerged as a significant model for the internationalization of higher education, garnering extensive attention in both domestic and international academic circles in recent years. This study utilizes data from China National Knowledge Infrastructure (CNKI) and Scopus to retrieve literature from 2014 to 2024 with "IaH" as the theme, resulting in 564 Chinese articles and 676 English articles. Through statistical analysis of publication quantities and high-frequency word analysis, the study reveals the characteristics and development trends of IaH research. The findings indicate that while there are commonalities in research focuses and perspectives between domestic and international academia, differences also exist. The international academic community places greater emphasis on cultivating intercultural competence, curriculum internationalization, and teaching innovation, whereas Chinese scholars tend to focus more on policy orientation and local practices, particularly in promoting IaH in local universities and implementing Sinoforeign cooperative education programs. Furthermore, the COVID-19 has significantly accelerated IaH research, with virtual exchanges and online teaching becoming focal points, highlighting the importance of digital means in internationalization practices. Based on these findings, this paper suggests that future research should strengthen the localization of IaH theoretical frameworks, explore the sustainable development of digital internationalization, deepen the exploration of multi-level practical pathways, and promote cooperation and dialogue between domestic and international academic communities in the field of IaH. This study provides important references for theoretical innovation and practical development in IaH, as well as valuable insights for the diversified development of higher education internationalization in the post-pandemic era.